Volcano vol. 6 [videorecording]. - Dorling Kindersley Vision; Sachs, Andrew (London Dorling Kindersley Ltd., 1994)
Volcano explodes the myths sorrounding our planet's violent nature. Journey to the most inhospitable regions of the earth, where rock melts and all life trembles. Witness the destructive effects of volcanoes and earthquakes - and the life-giving results of their aftermath.
Eyewitness presents the ultimate natural history experience. The series takes the viewer on a dazzling wildlife tour, interweaving facts, history, anecdote, myth and legend with energy and homour. Fast-paced and full of stunning graphics, EYEWITNESS is an enriching experience for all ages.
Director: Sanjida O'Connell. Series Producer: Richard Thomson. Executive Producers: Simon Jollads and Eve Krzyzanowski. Series Editor: Bridget Sneyd
Keywords: Volcanoes; Earthquakes